2021
DOI: 10.1002/chem.202005046
|View full text |Cite
|
Sign up to set email alerts
|

Concentration‐Dependent Self‐Assembly of an Unusually Large Hexameric Hydrogen‐Bonded Molecular Cage

Abstract: The sizes of available self‐assembled hydrogen‐bond‐based supramolecular capsules and cages are rather limited. The largest systems have volumes of approximately 1400–2300 Å3. Herein, we report a large, hexameric cage based on intermolecular amide–amide dimerization. The unusual structure with openings, reminiscent of covalently linked cages, is held together by 24 hydrogen bonds. With a diameter of 2.3 nm and a cavity volume of ∼2800 Å3, the assembly is larger than any previously known capsule/cage structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Tiefenbacher et al 128 reported a large hexameric cage (Fig. 12C) based on intermolecular amido-amide dimerization.…”
Section: Multiple Hydrogen Bonding Systems and Nano-adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tiefenbacher et al 128 reported a large hexameric cage (Fig. 12C) based on intermolecular amido-amide dimerization.…”
Section: Multiple Hydrogen Bonding Systems and Nano-adhesionmentioning
confidence: 99%
“…(B) Molecular recognition via hydrogen bonding and the covalent crosslinking forming disulfide bonds 127. (C) Hexameric hydrogen-bonded molecular cage 128. (D) Capsule structure formed via hydrogen bonding directed self-assembly 129.…”
mentioning
confidence: 99%
“…The cage was demonstrated to encapsulate spherical C 60 and C 70 fullerenes through favorable dispersive and π−π-interactions between the guest and the aromatic rings in the cage cavity (Figure 87). 204 Markiewicz, Jenczak, and co-workers prepared a robust enantiopure octameric cage (252) 8 held together by 48 cooperative hydrogen bonds between the 252 monomers. The capsule structure was retained in both the solid state, where crystals were obtained by the slow evaporation of a chloroform solution, and also in solution in nonpolar solvents, such as deuterated 1,1,2,2-tetrachloroethane (TCE-d 2 ).…”
Section: Capsules and Cagesmentioning
confidence: 99%
“…Since the first works by Ružička, , macrocycles and, later on, covalent organic cage compounds have become essential compounds in chemistry, material chemistry, crystal engineering, and biochemistry. The continuous development of supramolecular chemistry has resulted in macrocyclic compounds being employed as molecular building blocks in molecular tectonics. This approach allows for the construction of capsules with large internal cavities and is capable of capturing neutral and charged species in addition polymeric structures, where the monomers are bound by noncovalent interactions. …”
Section: Introductionmentioning
confidence: 99%